The Moving Image: Research + Design Process - Fellows, Diane (ARCC Conference Repository, 2014)
As consumers and communicators of visual narratives, conducting film (cinema and digitalvideo) research and filmmaking as an integral part of the architectural design process supports the designer‘s ability to develop and communicate architecture's narrative content. A film and architecture theory seminar and undergraduate design studio considers how film narrative is structured, multiple events through time are juxtaposed, and point of view is communicated. Film is not used as an illustration-in-motion of design projects but as the intellectual core intention of design process. The author briefly introduces issues of place-making through research evidenced in the construction of the author's own film work, and how that work helps frame pedagogy. In the classroom, while film research, analysis, and practice are key components establishing design tactics, the foremost goal is developing visual literacy - for whom is the story told, why, and how is that story communicated? This question allows for discerning perceptions and depth of reflection. Three studio project themes are developed through film analysis and making: The Horizon Line, Dreams and Materiality, Action/Engagement and Consequences. This essay considers the studio process by examining Alain Resnais' Hiroshima Mon Amour; Alejandro González Iñárritu's Babel Terrence Malick's Days of Heaven; Maya Deren's Meshes of the Afternoon, and Michael Hanake's Caché with student work referenced. Studio self-initiated gallery installation and symposium leads the author to a contemplative conclusion regarding the promise and efficacy of film research and making in the architectural design process.